Arabic Language Learning Syntax in Madrasah Diniyyah Takmiliyyah - Asep Nuhdi; Maswani Maswani (Green Publisher Indonesia, 2025)
The development of Arabic teaching methods can be carried out by a creative and innovative teacher who always pays attention to the principles of language teaching and is able to collect ideas or ideas to mix from ordinary to extraordinary things. The focus of this research is on the concept of developing language learning methods. Arabic at Madrasah Dinoyyah Takmiliyyah is then applied in learning Arabic. This research material was also expanded with the development of Arabic language learning methods that had been carried out in Indonesia as a comparison between theory and its realization in Indonesia. The research method in this research was the type of research used, namely library research and field research. The use of this approach is adapted to the main objectives of the research, namely to describe and analyze the development of Arabic language learning methods and to be transformed in Madrasah Diniyyah Takmiliyyah. The results and discussion are that if the purpose of learning Arabic is to make students proficient in Arabic which is characterized by mastery of the four language skills , then the methods and methods used must be adapted to that purpose. At least to make students proficient in the four skills is to use the syam'iyyah syafawiyyah method for listening and speaking. Also coupled with the deliberation method. For reading skills is the qira'ah method. Meanwhile, writing skills use imla techniques and drill/practice methods.